Performance analysis of biodegradable composite using polyvinyl alcohol and pomegranate peel powder for sustainable dry packaging applications - N. Abinaya; P. Sivaranjana; N. Rajini; Kumar Krishnan (Discover Materials)
Abstract This study focuses on the fabrication of a biodegradable dry packaging material for fruits, vegetables, and flowers, with an emphasis on affordability for street vendors. Approximately 55% of waste originates from packaging materials. To address this issue, a biodegradable Polyvinyl alcohol/Pomegranate peel powder (PVA/PPP) composite film was fabricated. The PVA, a water-soluble synthetic biodegradable polymer, served as the matrix, while PPP, an agro-waste product, was used as the filler. The PVA/PPP films were characterized through optical microscopy, FTIR, XRD, TGA, DSC, moisture absorption analysis, water vapour transmission rate (WVTR), water vapour permeability (WVP), and oxygen permeability testing. The inclusion of PPP enhanced the film’s properties via increasing moisture absorption by 85%, reducing PVA crystallinity index from 33.2 to 17.5%, percentage crystallinity reduced from 73.90 to 0.57%, lowering WVTR from 0.063 to 0.042 g/h.m2, low oxygen permeability and improving thermal stability up to 423 °C. Additionally, the pH of PPP (4.5) contributed to microbial resistance. The fabricated PVA/PPP films were fully biodegradable and produced via green synthesis without any hazardous chemicals. The use of PPP as a filler not only improved film performance but also reduced environmental hazard, demonstrating the material’s suitability for sustainable packaging applications.